Patient satisfaction on waiting time and duration of consultation at Orthopedic Clinic, Universiti Kebangsaan Malaysia Medical Centre - Raja Lexshimi RG,; Zaleha MI,; Shamsul AS,; Suriawati G, (Penerbit UKM, 2009)
Patients are increasingly dissatisfied with the “waiting time” and “duration of consultation” at outpatient clinics. A cross sectional study was carried out to measure waiting time and duration of consultation and to examine patients’ level of satisfaction towards waiting time and duration of consultation at the Orthopedic Clinic, Universiti Kebangsaan Malaysia Medical Centre (UKMMC). This study also examined patient’s satisfaction towards the overall clinic services. Data was collected using a self-administered questionnaire. A total of 81 patients participated in this study with a response rate of 100 percent. Findings indicated a significant difference in the mean between expected waiting time level II (from the time the patient is given the calling number till the time patient is called into the doctor’s room) and the actual waiting time level II experienced. A significant difference in the mean between the expected duration of consultation and the actual duration of consultation experienced was also noted. However, no significant difference was found between the mean of expected waiting time level I (the time patient register at the counter till the patient is given the calling number) and the actual waiting time (p>0.05). Overall, patient satisfaction towards waiting time was low (29.6%) and duration of consultation was of moderate level (41.9%). The overall satisfaction towards the clinic services were of average level (56.8%). Findings also indicated that patient satisfaction was not influenced by socio-demographic factors of respondents such as age, ethnic, education level, occupation and income level. Important findings from this study may help staff managing the clinic in addressing patients’ complaint on waiting time and improve patients’ satisfaction on the overall services of the Orthopedic clinic in UKMMC.